A review on the application of chicken immunoglobulin Y in aquaculture - Zhang, Linpeng; Lin, Li; Qin, Zhendong (Reviews in aquaculture, 2024)
The widespread use of antimicrobial drugs in aquaculture has led to antibiotic residues in aquatic animals. Food safety problems caused by the misuse of antibiotics and antibiotic residues have caused widespread global concern. Consequently, there is an urgent need to develop an alternative to antibiotics for use in aquaculture. Immunoglobulin Y (IgY) has attracted significant attention over recent years because it is readily available, simple to prepare, effective in inhibiting pathogenic microorganisms, free from environmental contamination and free from other toxic side effects. In this paper, we review the research progress relating to the basic structure, physicochemical properties and mechanism of action of IgY. We also highlight the applications of IgY in the control of aquatic animal disease, immunological diagnosis and the preservation of aquaculture products, thus providing a reference for future research and the wider application of IgY in aquaculture.